2014
DOI: 10.1007/s11292-014-9209-4
|View full text |Cite
|
Sign up to set email alerts
|

Crime displacement: what we know, what we don’t know, and what it means for crime reduction

Abstract: Objectives If offending were simply displaced following (often spatially) focused crime reduction initiatives, the continued expenditure of resources on this approach to crime reduction would be pointless. The aims of this article were to: critically appraise the current body of displacement research; identify gaps in understanding; articulate an agenda for future research; and to consider the implications of the accumulated findings for practitioners, evaluators, and policy makers. Methods First, we review ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(76 citation statements)
references
References 30 publications
7
62
0
7
Order By: Relevance
“…For brevity, Table 1 summarizes the features of SRs that should be attended to in high-quality studies. To these we add (in the final row of Table 1) the assessment of unanticipated outcomes (e.g., quantification of crime displacement or a diffusion of crime control benefit, see Johnson et al 2014). Table 2 lists the types of evidence (referred to as 'EMMIE-E') that should be included in an SR to inform understanding of an intervention and on which assessments of quality should be based.…”
Section: E -Effects: Overall Effect Direction and Sizementioning
confidence: 99%
“…For brevity, Table 1 summarizes the features of SRs that should be attended to in high-quality studies. To these we add (in the final row of Table 1) the assessment of unanticipated outcomes (e.g., quantification of crime displacement or a diffusion of crime control benefit, see Johnson et al 2014). Table 2 lists the types of evidence (referred to as 'EMMIE-E') that should be included in an SR to inform understanding of an intervention and on which assessments of quality should be based.…”
Section: E -Effects: Overall Effect Direction and Sizementioning
confidence: 99%
“…What is not clear is what degree of concentration of crime is preferable. Crime prevention strategies might result in some displacement of crime (Guerette and Bowers 2009;Johnson et al 2014) from one place to the other, to an alternative victim (which is referred to as target displacement), to different times of the day, to a different tactic or to a different type of crime (Bowers and Johnson 2003), which has an effect on the levels of concentration of crime, but then this promotes the question: is it desirable to have less concentrated crime? Clearly, a population with overall less crime is desirable, but let us compare two populations with the same number of crimes.…”
Section: Less or More Concentrated?mentioning
confidence: 99%
“…More commonly, it has been found that the opposite, a diffusion of crime reduction benefits in nearby areas not targeted by interventions, occurs at a rate that is about equal to observations of displacement. (Johnson et al, 2014) A corollary to the case for concentration is the need for coordination among selected programs. Unfortunately, there is little practical guidance for policymakers on how to identify the right mix of interventions and how to coordinate them effectively (Abt, 2014).…”
Section: Making the Case For Accumulation Concentration And Coordinmentioning
confidence: 99%